Odpowiedzi

Najlepsza Odpowiedź!
2009-10-26T19:59:05+01:00
1zad.

2 * 5²⁰-5¹⁸
------------- =
25⁹

5¹⁸ *(2 * 5² - 1)
-------------------- =
(5²)⁹

5¹⁸ *(2 * 5² - 1)
-------------------- =
5¹⁸

2 * 5² - 1 = 2 * 25 - 1 = 50 - 1 = 49


2zad.
(2¹⁹+2¹⁸) * 3²
------------------- =
(2¹⁸+2¹⁷) * 27

(2¹⁷⁺²+2¹⁷⁺¹) * 9
------------------------- =
(2¹⁷⁺¹ + 2¹⁷) * 27


2¹⁷ * (2²+2¹)
----------------------- =
2¹⁷ * (2¹+1) * 3

2²+2¹
-----------------=
(2¹+1) * 3

4+2
-----------=
3 * 3

6/9 = 2/3

3zad.

[(1½)⁻¹-3⁻²]⁻² = [(3/2)⁻¹-3⁻²]⁻² = [(2/3) -3⁻²]⁻² =
[(2/3) -(1/9)]⁻² = [(6/9) -(1/9)]⁻² = [5/9]⁻² = 81/25

4zad.
1⁻¹+2⁻¹+3⁻¹
------------------- =
(¾)⁻¹+3⁻¹*2

1+1/2+1/3
------------------- =
(4/3)+(1/3) *2

6/6+3/6+2/6
------------------- =
(4/3)+(2/3)

11/6
------- =
6/3

11/6
------- = 11/12
2